Mobile Gaming EMG-Based Brain Computer Interface - AlBayaa, Mohammad (2024)
Brain Computer Interface (BCI) has demonstrated significant effectiveness in optimizing the usability of mobile applications, particularly in the realm of mobile gaming. With the increasing popularity of video games, they offer an opportune platform for exploring novel control interfaces for mobile devices. This paper introduces the Mobile Gaming Electromyography (EMG)-Based Brain Computer Interface (MGaming EMG-BCI), which aims to enhance the user experience and address challenges related to input methods, gestures, accessibility, and inclusivity associated with conventional mobile device usage in mobile gaming. The system improves device usability by offering a new input method and gestures that players can utilize to interact with the game without the requirement of maintaining a fixed posture alleviating neck stiffness commonly associated with GUI-based mobile gaming. This expands the accessibility of games for different groups of players. Furthermore, it opens up opportunities for game developers to innovate and explore new possibilities in game design. The proposed interface integrates a BCI system with a game using EMG signaling, enabling real-time communication between the BCI and the game through a database. This integration allows users to interact with the game in a hands-free manner, alleviating the need for physical touch input. The results of this study indicate that the proposed BCI Mobile Gaming Interface has the potential to serve as a universal control scheme that can be seamlessly applied to a diverse range of games.